PENGUATAN SULAM OTOMATIS BERBASIS INOVASI, LITERASI NUMERASI, DIGITAL MARKETING UNTUK KEMANDIRIAN EKONOMI MASYARAKAT - Rusmini Rusmini; Kartika Sari Lubis; Linda Wahyuni; Kayla Khairani; Dinda Prasasti; Aizat Ramadhan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Automated embroidery holds significant potential to support community economic development. However, many automated embroidery entrepreneurs still face challenges related to product innovation, financial management, and the use of digital marketing. This community service program aims to strengthen the capacity of automated embroidery entrepreneurs through training in innovation, numeracy, and digital marketing. This program was implemented at the Nurul Hasanah Automatic Embroidery Business Group, located in Saentis Village, Percut Sei Tuan Subdistrict, Deli Serdang Regency, North Sumatra, Indonesia. The implementation method consisted of five stages: situation analysis, program planning, training and mentoring, practical implementation, and evaluation. Training activities focused on innovation in automatic embroidery design, financial management based on numeracy literacy, and digital marketing using social media platforms. The results of the activities showed that participants were able to develop a more diverse range of automatic embroidery products, improve their understanding of business calculations, and utilize digital platforms for product promotion. Participant motivation increased by 7.19%, from 57.24% before the training to 64.43% after the activities, indicating an increase in participants' motivation and engagement. This program contributed positively to strengthening entrepreneurial capacity and expanding market opportunities. Therefore, integrating innovation, numeracy literacy, and digital marketing can be an effective strategy to enhance community economic sustainability and independence. ABSTRAK Sulam otomatis memiliki potensi besar untuk mendukung pembangunan ekonomi masyarakat, namun mitra pelaku usaha masih menghadapi tantangan terkait inovasi produk, pengelolaan keuangan, dan pemanfaatan pemasaran digital. Program pengabdian kepada masyarakat ini bertujuan memperkuat kapasitas mitra usaha sulam otomatis melalui pelatihan inovasi, literasi numerasi, dan digital marketing. Pelaksanaan program bertempat di Kelompok Usaha Sulam Otomatis Nurul Hasanah di Desa Saentis, Kecamatan Percut Sei Tuan, Kabupaten Deli Serdang, Sumatera Utara. Metode implementasi mencakup lima tahapan: analisis situasi, perencanaan program, pelatihan dan pendampingan, implementasi praktis, serta evaluasi program. Kegiatan difokuskan pada pembaruan desain sulam, pengelolaan keuangan berbasis numerasi, dan promosi melalui media sosial. Hasil kegiatan menunjukkan mitra mampu mengembangkan variasi produk yang lebih beragam, meningkatkan pemahaman perhitungan bisnis, serta memanfaatkan platform digital secara optimal. Motivasi mitra mengalami peningkatan sebesar 7,19% yaitu dari 57,24% sebelum pelatihan menjadi 64,43% setelah kegiatan diselesaikan. Program ini berkontribusi positif dalam memperkuat kapasitas kewirausahaan serta memperluas jangkauan pasar mitra. Integrasi inovasi, literasi numerasi, dan digital marketing menjadi strategi efektif dalam menciptakan keberlanjutan dan kemandirian ekonomi masyarakat.